Pemilihan Area Pengembangan Ruang Terbuka Hijau Menggunakan Metode AHP dan TOPSIS di Kota Yogyakarta - Nita Handayani; Budi Kamulyan (Publikasi Indonesia, 2022)
The Sustainable Development Goals (SDGs) program is a world development agenda that aims to optimize the potential of human welfare resources globally. One such program is sustainable development in the form of green open spaces. The basis for Green Open Space (RTH) regulations is Law Number 26 of 2007 on Spatial Planning and Regulation of the Minister of Public Works Number 5 of 2008. The minimum requirement for green open space in a city is 30% of the total area. The City of Yogyakarta has increased the area of ​​green open space to prevent shrinkage of the area due to the impact of development into a commercial area and as an anticipation of disaster. This study selected the best green open space development areas in the city of Yogyakarta using the AHP and TOPSIS methods. The decision-making analysis method used in this study is AHP-TOPSIS. The results of the analysis stated that the total green open space of Yogyakarta City was 23.7% of the total area with 8.2% public green open space and 15.5% private green open space. By considering the 3 criteria and 10 sub-criteria for the 4 alternatives, it is known that the assessment of technical criteria is considered more important than economic and environmental. While the results of the comparison of the sub-criteria stated that the area is more considered with a weight of 0.187 compared to the other sub-criteria. The largest alternative preference value is the Umbulharjo Kemantren at 0.638, the Kotagede Kemantren with a preference value of 0.587. Kemantren Gondokusuman with a preference value of 0.487. As well as Kemantren Danurajen with a preference value of 0.347. Based on the 4 alternatives offered, the Umbulharjo Kemantren was selected and deserves to be recommended as an area for the Yogyakarta City Green Open Space development.